Amiens/Samarobriva, cité des Ambiens : aux origines de la ville romaine - Didier Bayard (Gallia)
The question of Samarobriva’s origins and early times has been studied on several occasions in the last decades. Its overall storyline has been defined in 1983 and shows two paradoxes. The first is related to its origins: despite the mention of its Celtic-sounding name in the De Bello Gallico or Cicero’s correspondence, no tangible link could be established between the Roman city and a previous Gallic town, or even a Caesarian camp.The building of the North Sea road, maybe during Agrippa’s second rule in Gaul between -19 and -16, seems to be at the root of a settlement at the edge of the Somme river. We found the road, extremely well-preserved, in the bottom of the valley. This settlement took on the appearance of a city organized by an even street layout between the end of Augustus’s reign and the middle of the 1st c. AD. Our analysis of the overall map shows this layout resulted from a coherent guiding plan, validating the hypothesis of an initial founding gesture. The main question remaining today is the datation of this founding. The setting up of the flint and gravel roads, except from two roads in the center of the city, has been dated to the years 50 AD, which match a critical moment in the city history; but several hints suggest the settlement was already vast at the end of Augustus’ reign, with housings organized according to that same guiding plan. We will see how and to which extent we can overcome those difficulties from the available documentation.